Genetic modifiers of cardiorespiratory fitness response to lifestyle intervention - Peter, Inga; Papandonatos, George D; Belalcazar, L Maria; Yang, Yao; Erar, Bahar; Jakicic, John M; Unick, Jessica L; Balasubramanyam, Ashok; Lipkin, Edward W; Delahanty, Linda M; Wagenknecht, Lynne E; Wing, Rena R; et al. (Medicine and science in sports and exercise, 2014)
Numerous prospective studies indicate that improved cardiorespiratory fitness reduces type 2 diabetes risk and delays disease progression. We hypothesized that genetic variants modify fitness response to an intensive lifestyle intervention (ILI) in the Action for Health in Diabetes (Look AHEAD) randomized clinical trial, aimed to detect whether ILI will reduce cardiovascular events in overweight/obese subjects with type 2 diabetes compared with a standard of care. Polymorphisms in established fitness genes and in all loci assayed on the Illumina CARe iSelect chip were examined as predictors of change in MET level, estimated using a treadmill test, in response to a 1-yr intervention in 3899 participants. We identified a significant signal in previously reported fitness-related gene RUNX1 that was associated with 1-yr METs response in ILI (0.19 ± 0.04 MET less improvement per minor allele copy; P = 1.9 × 10(-5)) and genotype-intervention interaction (P = 4.8 × 10(-3)). In the chipwide analysis, FKBP7 rs17225700 showed a significant association with ILI response among subjects not receiving beta-blocker medications (0.47 ± 0.09 METs less improvement; P = 5.3 × 10(-5)) and genotype-treatment interaction (P = 5.3 × 10(-7)). The Gene Relationships Among Implicated Loci pathway-based analysis identified connections between associated genes, including those influencing vascular tone, muscle contraction, cardiac energy substrate dynamics, and muscle protein synthesis. This is the first study to identify genetic variants associated with fitness responses to a randomized lifestyle intervention in overweight/obese diabetic individuals. RUNX1 and FKBP7, involved in erythropoesis and muscle protein synthesis, respectively, are related to change in cardiorespiratory fitness in response to exercise.